2014
DOI: 10.1364/josab.31.000376
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled oriented crystallization in SiO_2-based glasses by femtosecond laser irradiation

Abstract: 3D nano-crystallization has been investigated with a femtosecond laser beam in 33Li 2 O-33Nb 2 O 5 -34SiO 2 glass by changing the pulse energy and polarization direction. Electron backscattered diffraction was used to characterize the size and the orientation of crystals in cross sections of laser tracks, while second harmonic generation was employed to investigate the nonlinear optical properties of laser lines macroscopically. We are the first, to the best of our knowledge, to reveal that crystals of nano-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…First, decreasing the power density reduces the crystallized volume, in agreement with the results of ref. 17. In addition, consistent with the results shown at 243 GW/m 2 in Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…First, decreasing the power density reduces the crystallized volume, in agreement with the results of ref. 17. In addition, consistent with the results shown at 243 GW/m 2 in Fig.…”
Section: Resultssupporting
confidence: 92%
“…The correlation between laser scanning speed and crystal grain size presented in Figs 1(a) and 2(a) can explain why He et al 17. did not observe the formation of single crystal lines.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, the laser‐induced crystallization technique using cw Yb:YVO 4 fiber laser was applied to pattern LiNbO 3 crystals at the surface of NiO‐doped 40Li 2 O‐32Nb 2 O 5 ‐28SiO 2 glasses. The patterning of LiNbO 3 crystals in glasses by femtosecond (fs) laser irradiation has been also reported so far . For example, Cao et al reported the preferential nanocrystal orientation of LiNbO 3 using Yb‐doped fiber amplifier fs laser (λ = 1030 nm, pulse duration 300 fs, repetition rate 250 kHz, linearly polarized) in 32.5Li 2 O‐27.5Nb 2 O 5 ‐40SiO 2 glass.…”
Section: Resultsmentioning
confidence: 86%
“…Assembling a half wave plate and a polarizing beam splitter cube, from 0.3 to 2.2 μJ/pulse, controlled pulse energy. SHG microscopy images of irradiated lines were taken with the same laser system below the threshold of glass modification …”
Section: Methodsmentioning
confidence: 99%
“…Yonesaki et al demonstrated that in LNS glass fs laser irradiation induced the migration of cations that constitutes the glass, locally modified chemical composition, and drove crystalline phase precipitation at micrometer scale. A LiNbO 3 phase was reported when crystallization occurred on submicro or nanometer scales, but not the silica‐rich counterpart . Therefore, we wonder whether a phase separation really occurs and if silica could be included in LiNbO 3 structure as LiNbO 3 exhibits quite a large departure from stoichiometry (i.e., as a matter of fact, LiNbO3 shows a large departure from stoichiometry when doping with transition metal elements).…”
Section: Introductionmentioning
confidence: 99%